2022
DOI: 10.1021/acsami.2c12195
|View full text |Cite
|
Sign up to set email alerts
|

High Mobility Two-Dimensional Electron Gas at the BaSnO3/SrNbO3 Interface

Abstract: Oxide two-dimensional electron gases (2DEGs) promise high charge carrier concentrations and low-loss electronic transport in semiconductors such as BaSnO 3 (BSO). ACBN0 computations for BSO/SrNbO 3 (SNO) interfaces show Nb-4d electron injection into extended Sn-5s electronic states. The conduction band minimum consists of Sn-5s states ∼1.2 eV below the Fermi level for intermediate thickness 6-unit cell BSO/6unit cell SNO superlattices, corresponding to an electron density in BSO of ∼10 21 cm −3 . Experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 59 publications
4
10
0
Order By: Relevance
“…Similarly, the total energy changes by less than 1.0 meV atom −1 when the k-point grids are increased to 14 × 14 × 14 and 14 × 14 × 1, for the bulk and interface, respectively. Using the DFT equilibrium structures, we calculated self-consistent ACBN0 Hubbard-U parameters for bulk BSO, SSO, and STaO (Hubbard-U parameters: BaSnO 3 : Ba = 3.96 eV, Sn = 0.04 eV, O = 8.8 eV; SrSnO 3 : Sr = 0.3 eV, Sn = 0.03 eV, O = 8.5 eV; SrTaO 3 : Sr = 0.01 eV, Ta = 1.1 eV, O = 7.6 eV), similar in magnitude to those reported previously for perovskites [16,42]. The computed Hubbard-U parameters of bulk BSO are identical to those reported in our previous work [16].…”
Section: Methodssupporting
confidence: 84%
See 4 more Smart Citations
“…Similarly, the total energy changes by less than 1.0 meV atom −1 when the k-point grids are increased to 14 × 14 × 14 and 14 × 14 × 1, for the bulk and interface, respectively. Using the DFT equilibrium structures, we calculated self-consistent ACBN0 Hubbard-U parameters for bulk BSO, SSO, and STaO (Hubbard-U parameters: BaSnO 3 : Ba = 3.96 eV, Sn = 0.04 eV, O = 8.8 eV; SrSnO 3 : Sr = 0.3 eV, Sn = 0.03 eV, O = 8.5 eV; SrTaO 3 : Sr = 0.01 eV, Ta = 1.1 eV, O = 7.6 eV), similar in magnitude to those reported previously for perovskites [16,42]. The computed Hubbard-U parameters of bulk BSO are identical to those reported in our previous work [16].…”
Section: Methodssupporting
confidence: 84%
“…Using the DFT equilibrium structures, we calculated self-consistent ACBN0 Hubbard-U parameters for bulk BSO, SSO, and STaO (Hubbard-U parameters: BaSnO 3 : Ba = 3.96 eV, Sn = 0.04 eV, O = 8.8 eV; SrSnO 3 : Sr = 0.3 eV, Sn = 0.03 eV, O = 8.5 eV; SrTaO 3 : Sr = 0.01 eV, Ta = 1.1 eV, O = 7.6 eV), similar in magnitude to those reported previously for perovskites [16,42]. The computed Hubbard-U parameters of bulk BSO are identical to those reported in our previous work [16]. We computed the ACBN0 Hubbard-U parameters of bulk STaO and SSO for both cubic and orthorhombic phases and found that the Hubbard-U parameters depend only weakly on phase and octahedral rotation (∼0.1 eV).…”
Section: Methodssupporting
confidence: 84%
See 3 more Smart Citations